Evaluación de dos técnicas de inseminación artificial (Intrauterina y cervical) en cerdas reproductoras del hato porcino ESPAM MFL - Cedeño Acosta, César Alejandro (2021)
The present study aimed to evaluate two artificial insemination techniques (intrauterine and cervical) in breeding sows from the ESPAM MFL pig herd. For this purpose, a descriptive investigation was implemented at El Limón site, Calceta city, Bolívar canton, Manabí province, where 20 sows previously dewormed, vitaminized and under adequate conditions for reproduction, were exposed to two insemination methods (intrauterine and cervical), in a descriptive design and the application of descriptive statistical analyzes and mean comparisons through Student's t test for independent samples at a level of 5% probability. The protocol included heat induction in sows with the regumate protocol (trenbolone altrenogest) for 5 days, evaluating the variables: conception percentage, fertility percentage, number of piglets per parturition and weight of the litter at birth. The results indicate a conception and fertility percentage of 100%, without significant statistical differences being determined. There were no statistically significant differences between insemination methods for the variable number of live piglets per litter. Regarding birth weight, statistically significant differences were found between the insemination methods. Intrauterine AI demonstrated obtaining a higher number of piglets per farrowing (additional 0.6 kg) and better birth weight (additional 0.1 kg). The results of the present study show that there are reproductive and productive benefits in the implementation of the intrauterine insemination method in relation to the cervical insemination method.